Скринінг рослин з антиоксидантною та геномопротекторною активністю - Джуренко, Н.І.; Паламарчук, О.П.; Гуніна, Л.М.; Бабенко, Л.П.; Олійник, С.А. (Видавничий дім "Академперіодика" НАН України, 2007)
The results of screening model researches of the mechanisms of action of plant extracts, which were not in common use as medicinal till now, on the oxidization of lipids in fractions of animal liver chromatine are presented. The antioxidant and genom protective properties of plants (Cerasus tomentosa, Schizandra chinensis, Eleutherococcus senticosus, Chaenomeles japonica, Actinidia kolomikta, Ziziphus jujuba, Morus alba, Cydonia obJonga, Viburnum opulus, Cornus mas, Elaeagnus multiflora, Pastinaca sativa) specify the successful subsequent investigations with the purpose to use the preparations of these plants in different branches of medicine, including sport medicine, where they can be ergogenic remedies.